Constructing healthcare services markets: networks, brokers and the China-England engagement - Brian Salter; Yiming Dong; Benjamin M. Hunter (BMC, 2022)
Abstract Background Healthcare services is an expanding international market with which national healthcare systems engage, and from which they benefit, to greater and lesser degrees. This study examines the case of the China-England engagement in healthcare services as a vehicle for illuminating the way in which such market relationships are constructed. Findings China and England have different approaches to the international healthcare services market. Aware of the knowledge and technology gaps between itself and the leading capitalist nations of the West in healthcare, as in other sectors, the Chinese leadership has encouraged a variety of international engagements to facilitate the bridging of these gaps including accessing new supply and demand relationships in international markets. These engagements are situated within an approach to health system development based on establishing broad policy directions, allowing a degree of local innovation, initiating and evaluating pilot studies, and promulgating new programmatic frameworks at central and local levels. The assumption is that the new knowledge and technologies are integrated into this approach and implemented under the guidance of Chinese experts and leaders. England's healthcare system has the knowledge resources to provide the supply to meet at least some of the China demand but has yet to develop fully the means to enable an efficient market response, though such economic engagement is supported by the UK's trade related departments of state. As a result, the development of China-England commercial relationships in patient care, professional education and hospital and healthcare service development has been led largely by high status NHS Trusts and private sector organisations with the entrepreneurial capacity to exploit their market position. Drawing on their established international clinicians and commercial teams with experience of domestic private sector provision, these institutions have built trust-based collaborations sufficiently robust to facilitate demand-supply relationships in the international healthcare services market. Often key to the development of relations required to make commercial exchange feasible and practicable are a range of international brokers with the skills and capacity to provide the necessary linkage with individual healthcare consumers and institutional clients in China. Integral to the broker role, and often supplied by the broker itself, are the communication technologies of telemedicine to enable the interaction between consumer and healthcare provider, be this in patient care, professional education or healthcare service development. Conclusions Although England's healthcare system has the knowledge required to respond to China's market demand and such economic engagement is supported and actively encouraged by the UK's trade related departments of state, the response is constrained by multiple domestic demands on its resources and by the limits of the NHS approach to marketisation in healthcare.